School Effects on Social Development of Preschool Children in Nigeria - Adeleke, Florence Oluwaseye; Adeyemi, Sunday Bankole (NIU Journal of Humanities, 2020)
Education is provided to give the child all round development â€“ socially, intellectually, culturally, and morally.  Contemporary educational efforts have been concentrated on the development of the intellect at the expense of other vital aspects of the totality of man. This type of lopsided provision of education will only lead the nation to the production of uneducated folks who are only literate, but morally bankrupt and a social misfit. This paper therefore, examined the influence of school effects on the social development of preschool children. Three hypotheses were formulated to guide the study based on the parameters of school effects and social development constructs. The study which consisted of 330 samples in all, involved 150 teachers, and 180 preschool children. The data collected by means of a self-constructed questionnaire, were thereafter analysed with the use of Chi â€“square statistic. Findings showed that there is a significant influence of school climate on the development of self-concept among preschool children (X 2 =11.02; P<0.05).There is also a significant influence of school leadership on the social development of preschool children (X 2 = 8.01; P<0.05). However, school curriculum showed no significant influence on the social development of preschool children (X 2 =6.05; P<0.05).It was concluded that the social development of preschool children is a matter that should be accorded adequate attention, as this determines the success or otherwise of a childâ€™s cognition and self-esteem. Keywords: Preschool Children, School Climate, School Curriculum, School Effects, School Administrative Leadership, Resources